ANALISIS SOSIAL-BUDAYA TERHADAP EKSISTENSI PERKAWINAN ANAK DI MASYARAKAT SUMENEP - Muhammad Nafis (USRAH: Jurnal Hukum Keluarga Islam, 2024)
Child marriage remains a social phenomenon in various regions of Indonesia, including Sumenep Regency, Madura. Despite the revision of Marriage Law No. 16 of 2019, which sets the minimum age for marriage, this practice continues to persist in several areas, including Sumenep.This study aims to analyze the persistence of child marriage traditions in Sumenep Regency by examining the underlying socio-cultural factors and their impact on adolescents' lives. This research employs a qualitative method with an ethnographic approach. Data were collected through in-depth interviews with adolescents who married at a young age, parents, traditional leaders, and local policymakers, as well as through participatory observations within the community.The findings reveal that child marriage in Sumenep Regency is driven by various factors, including strong traditions and customs within the patrilineal Madurese society. Economic conditions and low levels of education also contribute to the high prevalence of child marriage. Additionally, interpretations of religious values are often used to justify this practice.The consequences of child marriage are significant, affecting physical health, psychological well-being, and socio-economic conditions. Young girls who marry early are vulnerable to reproductive health complications, dropping out of school, and mental distress. Socio-economically, this practice reinforces the cycle of poverty and deepens gender inequality.To address this issue, interventions from the government and non-governmental organizations are essential through a holistic and contextual approach. Prevention efforts must consider local cultural values and involve collaboration between the government, traditional leaders, religious figures, and the community. Increasing access to education and economic empowerment is a crucial strategy to tackle the root causes of child marriage in Sumenep Regency. Keywords: Child marriage, patrilineal culture, health impact, poverty cycle